Classification of Tsunami Potential Based on Earthquakes in Indonesia Using the C4.5 Algorithm - Eni Irfiani; Arnoldus Pius Purnomo Raben Galla; Vivien Sufi Hadi; Muhammad Iqbal Syaputra; Sriyadi; Haryani; Dio Okta Rovelino (Jurnal Mantik, 2022)
Natural disasters are natural phenomena that are difficult to prevent or avoid. The tsunami disaster caused by the earthquake was a natural disaster with a large impact with many casualties and material and non-material losses. One of the efforts to help deal with the tsunami natural disaster with the help of the Data Mining method is to classify the potential for a tsunami caused by an earthquake in Indonesia based on the BMKG dataset so that the community and government are alert and able to reduce the impact. Classification technique to predict the potential occurrence of tsunami waves generated by earthquakes in Indonesia by applying the C4.5 algorithm. The results of data processing obtained a prediction of the potential for a tsunami based on the classification of the attribute magnitude of the earthquake strength at sea (SR) and the area where the earthquake occurred (KM). The results of model testing using the confusion matrix to classify the potential for a tsunami show an accuracy value of 99.96%.